Pteridophylla Triásicas del Norte de Chile. Parte II. Dejerseya Herbst, Linguifolium (Arber) Retallack y Yabeiella Oishi - Gnaedinger, Silvia Cristina (2004)
Triassic Pteridophylla from the north of Chile. 11. Genera Dejerseya Herbst, Linguifoliurn (Arber) Retallack and YabeieZIa Oishi. In this second contribution to the taxonomy ofincerlae sedis leaves itom northern Chile, the foilowing taxa are described: Dejerseya lobata (Jonas & dc Jersey) Herbst, Dejerseya luinensis (Johnston) Anderson & Anderson, and cf Dejersqya sp.; Linguifoliurn lillieanum Arber, Yabeiella bruiiebuschiana Oishi and an undetermined leaf types. Specimens are from: La Ternera Formation (several localitiesfrom Cerro La Ternera), Las Breas Formation (Locality Punta del Viento, area of Vicuña, east of La Serena) and El Puquén Formation (Locality Bahía de los Lobos, área of Los Molles. All this units are of Upper Triassic